2021
DOI: 10.1186/s12868-021-00622-7
|View full text |Cite
|
Sign up to set email alerts
|

Construction of competitive endogenous RNA network reveals regulatory role of long non-coding RNAs in intracranial aneurysm

Abstract: Background Rupture of intracranial aneurysm (IA) is the main cause of devastating subarachnoid hemorrhage, which urges our understanding of the pathogenesis and regulatory mechanisms of IA. However, the regulatory roles of long non-coding RNAs (lncRNAs) in IA is less known. Results We processed the raw SRR files of 12 superficial temporal artery (STA) samples and 6 IA samples to count files. Then the differentially expressed (DE) mRNAs, miRNAs, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…13 A recent study showed that COL1A1 and COL5A2 were significantly up-regulated in the aneurysm group and could effectively regulate phosphoinositide 3-kinase (PI3K)/Akt signaling pathway. 28 Similar to the results of previous studies, we found that the five genes involved in encoding collagen (COL5A2, COL1A1, COL11A1, COL5A1) were The genes affecting ECM structural constituent also include VCAN, POSTN and THBS2. VCAN is a chondroitin sulfate proteoglycan, which has five different subtypes (V0, V1, V2, V3, V4).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…13 A recent study showed that COL1A1 and COL5A2 were significantly up-regulated in the aneurysm group and could effectively regulate phosphoinositide 3-kinase (PI3K)/Akt signaling pathway. 28 Similar to the results of previous studies, we found that the five genes involved in encoding collagen (COL5A2, COL1A1, COL11A1, COL5A1) were The genes affecting ECM structural constituent also include VCAN, POSTN and THBS2. VCAN is a chondroitin sulfate proteoglycan, which has five different subtypes (V0, V1, V2, V3, V4).…”
Section: Discussionsupporting
confidence: 91%
“… 13 A recent study showed that COL1A1 and COL5A2 were significantly up-regulated in the aneurysm group and could effectively regulate phosphoinositide 3-kinase (PI3K)/Akt signaling pathway. 28 Similar to the results of previous studies, we found that the five genes involved in encoding collagen ( COL5A2, COL1A1, COL11A1, COL5A1 ) were all up-regulated in the intracranial aneurysm group, and may play an important role in maintaining normal extracellular matrix components.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have shown that lncRNAs can act as miRNA sponges in the ceRNA regulatory network and further regulate protein expression 10 . In recent years, more and more studies have focused on the role of lncRNA-related ceRNA regulatory networks in intracranial aneurysm [ 11 ], cerebral infarction [ 12 ], type 2 diabetes [ 13 ] and various types of cancer [ 14 , 15 , 16 ]. Several lncRNAs, such as lncRNA GM12371, lncRNA Evf2 and lncRNA Pinky, were reported to be involved in regulation of synaptic functions and neurodevelopment [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…And HOTAIR has been also shown to promote tumor progression by regulating miRNAs expression and function. For example, in Table 4 , Pan et al 85 verified that the regulatory mechanism between HOTAIR and hsa-mir-17 played an important role in ruptured intracranial aneurysm disease. Cao et al 86 verified that the regulatory mechanism between HOTAIR and hsa-mir-20a played an important role in liver cancer cells.…”
Section: Resultsmentioning
confidence: 99%